Preparation and Application of a Hydrochar-Based Palladium Nanocatalyst for the Reduction of Nitroarenes - Melike Çalışkan (MDPI AG, 2021)
In the present study, a novel heterogeneous catalyst was successfully fabricated through the decoration of palladium nanoparticles on the surface of designed Fe3O4-coffee waste composite (Pd-Fe3O4-CWH) for the catalytic reduction of nitroarenes. Various characterization techniques such as XRD, FE-SEM and EDS were used to establish its nano-sized chemical structure. It was determined that Pd-Fe3O4-CWH is a useful nanocatalyst, which can efficiently reduce various nitroarenes, including 4-nitrobenzoic acid (4-NBA), 4-nitroaniline (4-NA), 4-nitro-o-phenylenediamine (4-NPD), 2-nitroaniline (2-NA) and 3-nitroanisole (3-NAS), using NaBH4 in aqueous media and ambient conditions. Catalytic reactions were monitored with the help of high-performance liquid chromatography. Additionally, Pd-Fe3O4-CWH was proved to be a reusable catalyst by maintaining its catalytic activity through six successive runs. Moreover, the nanocatalyst displayed a superior catalytic performance compared to other catalysts by providing a shorter reaction time to complete the reduction in nitroarenes.